2017
DOI: 10.1186/s12889-017-4819-1
|View full text |Cite
|
Sign up to set email alerts
|

Is vegetarian diet associated with a lower risk of breast cancer in Taiwanese women?

Abstract: BackgroundStudies on the relationship between vegetarian diet and breast cancer in Asian populations are limited. This study aimed to investigate the relationship between vegetarian diet, dietary patterns, and breast cancer in Taiwanese women.MethodsThis case-control study compared the dietary patterns of 233 breast cancer patients and 236 age-matched controls. A questionnaire about vegetarian diets and 28 frequently-consumed food items was administered to these 469 patients in the surgical department of Taipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 50 publications
2
29
0
1
Order By: Relevance
“…These results show that ultra-processed food consumption and overweight were associated with breast cancer in this sample of Brazilian women, which is partially consistent with published studies [5,7,21,22]. Additionally, poor environmental sanitation and family history of cancer were identified as risk factors for breast cancer in these women.…”
Section: Discussionsupporting
confidence: 80%
“…These results show that ultra-processed food consumption and overweight were associated with breast cancer in this sample of Brazilian women, which is partially consistent with published studies [5,7,21,22]. Additionally, poor environmental sanitation and family history of cancer were identified as risk factors for breast cancer in these women.…”
Section: Discussionsupporting
confidence: 80%
“…Vegetables and their products were not taken as meals by cohort of subjects and controls, but rather as parts of meals in which carbohydrates is a predominant portion. Although, vegetables have been shown to be associated with lower risk of breast cancer by providing high-fibre diets, low in energy and fat (Chang et al, 2017;Catsburg et al, 2015;Mourouti et al, 2015;Lelièvre and Weaver, 2013), there is no consensus about their ultimate value nevertheless studies have found the consumption of soy products associated with a lower risk for breast cancer (Wu et al, 1998;Greenwald, 2002). Aside from this, there is also no consensus as regard to their value when it comes to breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…(44) Asyalı kadınlarda yapılan meta-analizde, yüksek soya alımı sonucu meme kanserine yakalanma riskinin daha düşük olduğu söylenmiştir. (45) Bitkisel bazlı diyetle yüksek oranda alınan lif, antioksidanlar, flavonlar, vitamin C, karotenoidler ve diğer fitokimyasallar, düşük doymuş yağ oranı, düşük alkol, sigara tüketimi bu sonuçlarla ilgili olabilir. (46) Bebek ve çocuklarda vegan-vejetaryen beslenme:…”
Section: Kanserunclassified